Задержка эвтрофикации путём удаления из воды биогенных элементов - Ульман, Д.; Рудольф, Г. (Гидробиологический журнал, 1966)
On designing purification plants, allowance must be made for biogenic factors (development of algae) on the self-purification process. The biogenic elements of waste waters, entering into the cycle, are utilized repeatedly and accordingly enhance algal development. Hence the capacity of the purification plants should be based on the values characterizing the nitrogen and phosphorus contents in the waste liquid. Biogenic elements are bound by soils and silts to a considerable extent, which furthers their removal from the cycle. Waste waters purified by biological methods frequently contain more than fifty per cent of the initial quantity of nitrogen and phosphorus. Repeated removal of biogens may be carried out by microbiological (denitrification) and chemical means, i. e. processing waste waters by compounds of trivalent iron, aluminium and calcium. Additional elimination of biogenic elements may be carried out most effectively in aerotanks, biological gutters and secondary setting tanks, in biological ponds, earth ditches and in special plants. Precipitants may also be used in open ditches and plastic absorption pipes. The purification of waste waters from biogenic elements is 100 times cheaper than the purification of polluted surface water and fighting «blooming».